Comparative study on passive design considerations on selected hospital designs in Malaysia - Mohd Nawawi, Norwina; Aripin, Srazali (2004)
Health is synonymous with hospitals as a place to attain care towards gaining wellness. Hospitals as one of the healthcare facility buildings, varies its design configuration and forms according to the needs and function including the geographical location of its placement for the society it serves. The sun, the wind, the waterways, the natural lighting, the natural building materials of timber and clay were the ingredient for most healthcare buildings of the world. The Malaysian hospitals are no different to these phenomena.